POST-ABORTION CARE -: CONCEPT PAPER - Elizabeth, Siraha; Gladys, Mugadza; Mary, Kasu Christine; Abigail, Kapfunde; Clara., Haruzivishe (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
There are varying perceptions by health care providers regarding what post-abortion care (PAC) is and its utilisation in reducing maternal morbidity and mortality. The concept is available but unclear hence, the researchers sought to clear variations and ambiguity among different authors regarding the concept of interest so that it can be objectively measured to enhance standardisation of care.